2021
DOI: 10.3150/20-bej1313
|View full text |Cite
|
Sign up to set email alerts
|

Minimax semi-supervised set-valued approach to multi-class classification

Abstract: In this work we study the semi-supervised framework of confidence set classification with controlled expected size in minimax settings. We obtain semi-supervised minimax rates of convergence under the margin assumption and a Hölder condition on the regression function. Besides, we show that if no further assumptions are made, there is no supervised method that outperforms the semi-supervised estimator proposed in this work. We establish that the best achievable rate for any supervised method is n −1/2 , even i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 11 publications
(18 citation statements)
references
References 39 publications
1
11
0
Order By: Relevance
“…This result is the main reason why our conclusions on the semi-supervised estimation is different from the ones in [5,18]. For instance, in [5] the authors also obtain a final decision rule by thresholding on some estimated level.…”
Section: Upper Boundmentioning
confidence: 63%
See 3 more Smart Citations
“…This result is the main reason why our conclusions on the semi-supervised estimation is different from the ones in [5,18]. For instance, in [5] the authors also obtain a final decision rule by thresholding on some estimated level.…”
Section: Upper Boundmentioning
confidence: 63%
“…Our analysis implies that in the setting of binary classification with F-score the semi-supervised techniques are not superior to the supervised ones. In contrast, in [5] the authors showed that in the context of confidence set classification semi-supervised classifiers might outperform it supervised counterparts. -From the theoretical point of view, the most relevant reference is a recent work of [23],…”
Section: Related Work and Contributionsmentioning
confidence: 95%
See 2 more Smart Citations
“…That is to say that the optimal set-valued classifier Γ * (F P ,C P ) exists, is unique, and is deterministic. We refer to (Chzhen, Denis and Hebiri, 2021;Sadinle, Lei and Wasserman, 2019a) for a broad discussion on the role of Assumption 1. In particular, (Sadinle, Lei and Wasserman, 2019a) describe a way to bypass this assumption by considering randomized set-valued classifiers.…”
Section: Main Set-valued Classification Frameworkmentioning
confidence: 99%